Islamic Reading Website as Authentic Material to Improve Reading Skills and Islamic Values - Dhian Marita Sari; Nunun Indrasari (At Turots: Jurnal Pendidikan Islam, 2022)
In this disrupted era, technology affects all aspects of human life, particularly education. Reading website is one of the online materials that can motivate and assist students and lecturers in the teaching-learning process. Islamic reading websites improve students' reading comprehension skills and encouragement of students’ Islamic values. The purpose of this study is to investigate the use of Islamic reading websites articles as authentic material in teaching reading comprehension of the third-semester students at STIT Madani Yogyakarta. The qualitative research method was used in this study. This study was carried out on the third-semester students. The collecting of data was obtained through observations and interviews. Based on the research, using Islamic websites as useful sources of information can help students improve their English skills. Furthermore, students' reading performance and Islamic values were constantly improved by their use of Islamic websites.